2006
DOI: 10.4049/jimmunol.176.5.3070
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte TLR4 Mediates Phagocytosis and Translocation of Bacteria Across the Intestinal Barrier

Abstract: Translocation of bacteria across the intestinal barrier is important in the pathogenesis of systemic sepsis, although the mechanisms by which bacterial translocation occurs remain largely unknown. We hypothesized that bacterial translocation across the intact barrier occurs after internalization of the bacteria by enterocytes in a process resembling phagocytosis and that TLR4 is required for this process. We now show that FcγRIIa-transfected enterocytes can internalize IgG-opsonized erythrocytes into actin-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
259
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 353 publications
(278 citation statements)
references
References 57 publications
9
259
0
10
Order By: Relevance
“…Given the current observation that mice in which TLR4 had been deleted from the intestinal epithelium (TLR4 Δvillin ) also had normal intestinal perfusion when subjected to experimental NEC, these findings raise the intriguing possibility that TLR4 signals first within the intestinal epithelium-where bacteria rich in TLR4 ligands are first encountered-which is then followed by activation within the endothelium leading to NEC. In support of this paradigm, we have demonstrated that TLR4 activation within the epithelium promotes bacterial translocation in two ways: by disrupting the intestinal barrier through increased enterocyte apoptosis and reduced mucosal repair (5,11) and through direct transcellular passage in which TLR4 mediates the uptake of TLR4 ligands by enterocytes (18). The subsequent activation of TLR4 within the endothelium then results in the impaired perfusion of the subjacent intestinal microcirculation through a reduction in eNOS, which leads to intestinal necrosis and the development of NEC.…”
Section: Discussionmentioning
confidence: 87%
“…Given the current observation that mice in which TLR4 had been deleted from the intestinal epithelium (TLR4 Δvillin ) also had normal intestinal perfusion when subjected to experimental NEC, these findings raise the intriguing possibility that TLR4 signals first within the intestinal epithelium-where bacteria rich in TLR4 ligands are first encountered-which is then followed by activation within the endothelium leading to NEC. In support of this paradigm, we have demonstrated that TLR4 activation within the epithelium promotes bacterial translocation in two ways: by disrupting the intestinal barrier through increased enterocyte apoptosis and reduced mucosal repair (5,11) and through direct transcellular passage in which TLR4 mediates the uptake of TLR4 ligands by enterocytes (18). The subsequent activation of TLR4 within the endothelium then results in the impaired perfusion of the subjacent intestinal microcirculation through a reduction in eNOS, which leads to intestinal necrosis and the development of NEC.…”
Section: Discussionmentioning
confidence: 87%
“…To do so, we treated the intestinal crypt-like cell line IEC-6, which we have previously shown to express TLR4 (5,11,23) with LPS and determined the subsequent effects on ER stress and apoptosis. As shown in Fig.…”
Section: Tlr4 Activation Induces Er Stress and Apoptosis In Iec-6 Entmentioning
confidence: 99%
“…In this regard, several investigators have established that DAMPs and PAMPs are recognized by TLRs in many cells, including epithelial cells: a list of the TLRs and their cognate ligands appears in Table 1. Although current dogma suggests that circulating leukocytes play a central role in the coordination of the immune response, emerging evidence suggests that the epithelium also plays a key role in the recognition and response to various "danger molecules" (27)(28)(29)(30)(31). This review will examine in detail the various roles of epithelial signaling via TLRs in the development of common, and often devastating, mucosal inflammatory conditions.…”
Section: Defining the Controversies In The Pathogenesis Of Mucosal Inmentioning
confidence: 99%